Extraction Optimization, Structure Analysis and Antioxidant Activity of Polysaccharide from Sanghuangporus baumii - Qu, Yunhe; Zhang, Pingping; Cui, Jing; Ni, Xiuzhen; Song, Kai; Shi, Dongfang (Current Analytical Chemistry, 2024)
Introduction: In this study, we optimized the extraction process, analyzed the structure and assessed the antioxidant activity of Sanghuangporus baumii polysaccharide (SBP). The present results provide important information for the Sanghuangporus baumii polysaccharides in potential natural antioxidant effects. Background: The extraction and structural analysis of polysaccharides from Sanghuangporus has gained significant attention in the fields of chemistry, medicine, and life sciences. There is great significance in maximizing the extraction of polysaccharides from Sanghuangporus and developing their potential products in a scientific and rational manner. Objective: The study was designed to establish an efficient and practical extraction process for SBP, and then investigated the structure and the antioxidant activity. Methods: The Response Surface Methodology (RSM) based on Box-Behnken design was used to explore the ultrasound-assisted extraction of SBP, and the structure of SBP was studied by ultraviolet spectroscopy, infrared spectroscopy and other instrumental analysis methods. The total antioxidant capacity of SBP was studied by the Ferric Reducing Ability of Plasma (FRAP) method, and the scavenging capacity of ABTS+·, DPPH· and OH· was carried out as the index to investigate its antioxidant activity in vitro. Results: The statistical analysis results showed that the optimal conditions for extracting SBP were an ultrasound time of 20.74 min, ultrasound power of 268.40 W and material-liquid ratio of 1:25.71. Under optimal conditions, the experimental yield of SBP was 3.36 ± 0.01%. The RSM optimization process was applied to the experiment of complex enzyme extraction of SBP, and the yield increased to 4.72 ± 0.03%. Structural analysis showed that SBP mainly consisted of glucose, a small amount of mannose and galactose, and the molecular weight distribution was uneven, mainly concentrating in the three parts of 24.5,6.4,2.5 kDa. Moreover, SBP exhibited dose-dependent and strong reducing power and radical scavenging activity. For DPPH·, ABTS+· and OH· radical scavenging assays, IC50 values were 1.505 ± 0.050 mg/ml, 0.065 ± 0.036 mg/ml and 0.442 ± 0.007 mg/ml, respectively. Conclusion: In the present study, a β-linked heteroglucan (SBP) was extracted using the optimized process combining enzymes from the fruiting bodies of Sanghuangporus baumii. SBP exhibited effective and dose-dependent antioxidant activities. Our findings were of great value in terms of developing polysaccharides with potential natural antioxidants.
Keywords: response surface methodology